Axiological Analysis of Islamic Education Philosophy in a Tahfidz Quran Boarding School - Mujiburrohma, Mujiburrohma; Mabruroh, Nurul (El-Rusyd, 2025)
Islamic education is not merely oriented toward knowledge transmission and skill development but also toward the internalization of values as the foundation of character formation. This study aims to analyze the philosophy of Islamic education at a Tahfidz Quran boarding school through an axiological approach from the perspective of Islamic philosophy. Employing a qualitative method with a philosophical approach, data were collected through document analysis, observation, and interviews. The findings reveal that the educational philosophy is grounded in the values of tawhid, Quranic ethics, sincerity, discipline, and responsibility, oriented toward the formation of the complete human being (insan kamil). From an axiological perspective, these values function not only as educational goals but also as normative principles guiding the entire educational process and students’ daily life. This study contributes to the discourse on Islamic education philosophy by highlighting the systematic integration of divine and human values within Quran-based boarding school education.